Vitamin D Deficiency in Patients with Chronic Liver Disease: A Clinical Study at A Tertiary Care Hospital - Islam Shah, Wiqas Ahmad, Farooque Islam, Muhammad Hanif Hadi, Jawad Mahmood, Muhammad Kashif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients with chronic liver disease (CLD) have deficiencies of multiple nutrients and compare to other nutrients vitamin D deficiency occurs more commonly in patients with CLD. Due to liver fibrosis, synthetic functions of the liver are reduced, leading to vitamin D deficiency through impaired activation via a reduction in vitamin D Binding Protein. Reduction in performance status and dietary deficiency further adds to the scenario The study assessed the frequency of vitamin D deficiency in chronic liver disease patients and its association with the severity of chronic liver disease. Methodology: The department of gastroenterology at the Hayatabad Medical Complex in Peshawar carried out this descriptive study. 141 CLD patients who satisfied the criteria were included in the research. Three groups of patients were divided based on their Child-Pugh scores. The patient's vitamin D levels were examined by hospital laboratories. Serum (25,OH)D concentrations below 30 nmol/L were considered to represent [vitamin D] insufficiency levels. The data were examined using SPSS version 22. Results: 141 CLD patients were assessed. In this study the (mean age) was 53.40 ± 12.194 .years. The (male-to-female ratio) was 2.4:1. Hepatitis C was the underlying etiology in 56.7% of CLD patients. 83 patients (58.9%) had Child-Pugh Class C chronic liver disease. Ninety-five patients (67.4%) had low vitamin D levels. Vitamin D insufficiency correlated with gender and (Child-Pugh Class) Conclusion: Patients with liver cirrhosis are frequently vitamin D deficient. In our study, 67.4% patients were found to have deficient vitamin D levels. Vitamin D deficiency was more common in females and those with advanced liver fibrosis. Keywords: Vitamin D deficiency, Vitamin D level, Fibrosis, Chronic liver disease (CLD)